METHODS OF TEACHING READING COMPREHENSION FOR ESL AT MTS FAJAR SIDDIQ - Novianty, Melisa; Fadly, Muhammad Fahmi (Prodi Pendidikan Bahasa Inggris Universitas Palembang, 2024)
Reading is one way to enable students and teachers to broaden their horizons in thinking and behaving. The more you read, the better you will be in all your actions in daily life. In this case, the writer gives information for some methods of teaching reading comprehension for English Second Languagu (ESL). Therefore, the teachers can use the methods when they teach about reading. Hopefully, these methods will not only make the studensts but also Eglish teachers enthusiastic in learning reading comprehension. Besides, this ESL focus to junior high school students. The teachers of English teach reading by giving some methods in learning process. Moreover, the writer gave questionnaire for the students to know about the condition in their class. The result of questionnaire showed that 52.9 % students like to study and 52.9% like to read English. Therefore, in this case, the teacher of English should give high motivation and introduce the method of learning English, especially Readiing comprehension achievement. In order, the students will love to read in English more.